2015
DOI: 10.3402/fnr.v59.28646
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre intakes and reduction in functional constipation rates among Canadian adults: a cost-of-illness analysis

Abstract: BackgroundEvidence-based research highlights beneficial impacts of dietary fibre on several aspects of the gut pathophysiology that are accompanied by a considerable financial burden in healthcare services. Recommended intakes of dietary fibre may thus associate with financial benefits at a population level.ObjectiveWe sought to systematically assess the potential annual savings in healthcare costs that would follow the reduction in rates of functional constipation and irregularity with increased dietary fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Despite dietary guidelines and recommendations, dietary fiber intake by the population of the United States remains low [ 1 ], with less than 10% meeting the recommended levels for fiber intake [ 2 , 3 ]. Similar findings for low fiber intake among Canadian adults have been linked with constipation [ 4 ]. With the connection between fiber intake and the benefits for normal laxation, it is not surprising that an estimated 20% of the U.S. population has chronic constipation.…”
Section: Introductionsupporting
confidence: 76%
“…Despite dietary guidelines and recommendations, dietary fiber intake by the population of the United States remains low [ 1 ], with less than 10% meeting the recommended levels for fiber intake [ 2 , 3 ]. Similar findings for low fiber intake among Canadian adults have been linked with constipation [ 4 ]. With the connection between fiber intake and the benefits for normal laxation, it is not surprising that an estimated 20% of the U.S. population has chronic constipation.…”
Section: Introductionsupporting
confidence: 76%
“…Evidence from prospective studies shows cereal fibre specifically reduces the risk of colorectal cancer [ 52 ], diverticular disease [ 53 ], weight gain [ 54 , 55 ] and all-cause mortality [ 34 ]. In addition, modelling studies in the US [ 56 ] and Canada [ 57 ] have demonstrated substantial savings in medical costs from a reduction in constipation with increased dietary fibre consumption, for which some types of cereal fibre are considered particularly efficacious [ 58 ]. Furthermore, our findings are modelled based on a population who are free of CVD and T2D, and not to those who already have these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, limitations are worth noting. First, while recent literature and national databases were reviewed for identification of consumer trends and healthcare-related costs, as with previous cost-of-illness analyses [ 54 , 81 , 82 ], isolating the effects of pulses from other elements of lifestyle is challenging.…”
Section: Discussionmentioning
confidence: 99%